2013
DOI: 10.1148/radiol.13122053
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Carcinoma: Quantitative Biexponential MR Imaging Relaxometry Reveals the Dynamic Recruitment of Ferritin-expressing Fibroblasts to the Angiogenic Rim of Tumors

Abstract: Purpose:To quantitatively monitor the dynamic perivascular recruitment of ferritin heavy chain (FHC)-overexpressing fibroblasts to ovarian carcinoma xenografts by using R2 mapping and biexponential magnetic resonance (MR) relaxometry. Materials andMethods:In vivo studies of female mice were approved by the institutional animal care and use committee. In vitro analysis included MR-based R2 relaxation measurements of monkey kidney cell line (CV1) fibroblasts that overexpress FHC, followed by inductively coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…Previously, some studies have reported on the imaging of tumor-associated stroma (9,13,22,30,31). Ko et al (4) showed that apparent diffusion coefficient values were lower in the stroma-poor group than in the stroma-rich quantified with immunohistochemistry; this finding supported our hypothesis that DCE CT had the potential to depict a similar spatial distribution of tumor-associated stroma to that confirmed with histopathologic analysis.…”
Section: Relationship Between Tumor Hypoxia and Other Parameterssupporting
confidence: 87%
See 2 more Smart Citations
“…Previously, some studies have reported on the imaging of tumor-associated stroma (9,13,22,30,31). Ko et al (4) showed that apparent diffusion coefficient values were lower in the stroma-poor group than in the stroma-rich quantified with immunohistochemistry; this finding supported our hypothesis that DCE CT had the potential to depict a similar spatial distribution of tumor-associated stroma to that confirmed with histopathologic analysis.…”
Section: Relationship Between Tumor Hypoxia and Other Parameterssupporting
confidence: 87%
“…Thus, there is a strong need for reliable biomarkers and noninvasive in vivo imaging strategies for the stromal components. However, to date, it has not been possible to use conventional imaging techniques to assess tumor stromal components in clinical practice even though considerable efforts have been devoted to the development of novel imaging techniques (4,8,9).…”
Section: Implication For Patient Carementioning
confidence: 99%
See 1 more Smart Citation
“…Ftn reporter genes were applied in a wide range of MRI studies including the detection of viral-based gene transfer as a surrogate of gene therapy, monitoring of stem cells and migration of other cells in the context of regenerative medicine for the heart and brain, and monitoring recruitment of cells in cancer [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. As an endogenous protein, which can be used for generating detectable MRI contrast when expressed at physiological levels, Ftn offers the hope for its utilization for detection of transcriptional activation of gene expression, for detection of cell differentiation, and for longitudinal tracking of cell proliferation and migration.…”
Section: Nmr and Mri Studies Of The Ferritin Iron Corementioning
confidence: 99%
“…More recently, fibroblasts overexpressing ferritin heavy chain (FHC) were engineered and used to quantitatively monitor the dynamic perivascular recruitment in ovarian carcinoma xenografts (Vandsburger et al, 2013). FHC overexpression combined with R 2 mapping and MR relaxometry enabled in vivo imaging of the recruitment of exogenously administered fibroblasts to the vasculature of ovarian tumor xenografts (Vandsburger et al, 2013).…”
Section: Stromal Components Of the Tme And Their Role In Pmmentioning
confidence: 99%